ROBUST DESIGN IN GENERALISED LINEAR MODELS FOR IMPROVING THE QUALITY OF POLYURETHANE SOLES - Mares Castro, Armando; Dominguez, Jorge (The South African Journal of Industrial Engineering, 2015)
In a process that manufactures polyurethane soles by casting, a number of problems lead to different types of defects on the sole, causing significant economic losses for the company. In order to improve the product quality and decrease the number of defects, this study conducts an experimental design in the context of robust design. Since the response variable is binary, the statistical analysis was performed using generalised linear models. The operational methodology reduced the percentage of defects, while combining the experimental technique and control systems to achieve superior quality and a consequent reduction in costs.